Dysphagia screening and risks of pneumonia and adverse outcomes after acute stroke: An international multicenter study. Issue 2 (February 2020) - Ouyang, Menglu; Boaden, Elizabeth; Arima, Hisatomi; Lavados, Pablo M; Billot, Laurent; Hackett, Maree L; Olavarría, Verónica V; Muñoz-Venturelli, Paula; Song, Lili; Rogers, Kris; Middleton, Sandy; Pontes-Neto, Octavio M; et al.
Background: Dysphagia is associated with aspiration pneumonia after stroke. Data are limited on the influences of dysphagia screen and assessment in clinical practice. Aims: To determine associations between a "brief" screen and "detailed" assessment of dysphagia on clinical outcomes in acute stroke patients. Methods: A prospective cohort study analyzed retrospectively using data from a multicenter, cluster cross-over, randomized controlled trial (Head Positioning in Acute Stroke Trial [HeadPoST]) from 114 hospitals in nine countries. HeadPoST included 11, 093 acute stroke patients randomized to lying-flat or sitting-up head positioning. Herein, we report predefined secondary analyses of the association of dysphagia screening and assessment and clinical outcomes of pneumonia and death or disability (modified Rankin scale 3–6) at 90 days. Results: Overall, 8784 (79.2%) and 3917 (35.3%) patients were screened and assessed for dysphagia, respectively, but the frequency and timing for each varied widely across regions. Neither use of a screen nor an assessment for dysphagia was associated with the outcomes, but their results were compared to "screen-pass" patients, those who failed had higher risks of pneumonia (adjusted odds ratio [aOR] = 3.00, 95% confidence interval [CI] = 2.18–4.10) and death or disability (aOR = 1.66, 95% CI = 1.41–1.95). Similar results were evidence for the results of an assessment for dysphagia. Subsequent feeding restrictions were related to higher risk of pneumonia in patients failed dysphagia screen or assessment (aOR = 4.06, 95% CI = 1.72–9.54). Conclusions: Failing a dysphagia screen is associated with increased risks of pneumonia and poor clinical outcome after acute stroke. Further studies concentrate on determining the effective subsequent feeding actions are needed to improve patient outcomes.